Estudo da biossorção de flavonoides do bagaço de uva em Saccharomyces cerevisiae - Oliveira, Ann Lou Mucharski Strafit de (2019)
Wineries and Breweries produce large amount of agro-industrial wastes which can be reused. In the production of wines, the phenolic compounds present in grapes are not fully extracted, being discarded with pomace. In the production of beer, the yeast used in fermentation, Saccharomyces cerevisiae, can be reused, but part of your efficiency is lost, being necessary the replacement of the yeast during the process. Both industries generate, therefore, large amounts of waste, with high potential of reutilization. In this context, this study aimed to evaluate the use of yeast Saccharomyces cerevisiae as a biosorbent substrate for flavonoids extracted from the grape pomace of the varieties Merlot and Tannat. The yeast residue and the grape pomace were characterized by Scanning Electron Microscopy (SEM) where it was possible to verify the initial cell damage, being notorious after biosorption cells showed swollen and with small lumps in the surface area. In addition, the Medium Infrared Spectroscopy with Attenuated Total Reflectance (MIR/ATR) was used for the characterization and comparison of the samples. With spectroscopy analysis, the main functional groups were identified related to the biosorption, as groups, carboxyl and hydroxyl amino/amide. The phenolic content of hydroalcoholic extracts was identified via High-Performance Liquid Chromatography with diode array detector (HPLC-DAD). For the analysis of chromatography, preceded with the validation of the method, where they were assessed 5 flavonoids, and the same searched in the samples before and after the biosorption. However, the catechin was the only flavonoid found in the samples, with your peak reduced 16% and 50% for samples Merlot e Tannat biossorved. For the determination of total phenolic compounds (TPC), the method of the Folin-Ciocalteu reagent was used, while for the determination of flavonoids the methodology based in the aluminium chloride reagent was applied. For the Merlot variety, the flavonoids corresponded to about 24.5% of the CFT, while for the Tannat variety, this value approached 42% of the total phenolic compounds. For the biosorption assays, the equilibrium time was 4 hours, being applied the kinetic models of Pseudo - second order and intraparticle diffusion. The first model describes that the sorption rate is proportional to the number of free binding sites on the surface of the biosorbent material, and the second one considers that more than one factor can interfere with the adsorption, resulting in adsorption of several stages. Thus, the data were better fitted to the pseudo-second order model, with determination coefficients of 0.9968 and 0.9914 for the varieties Merlot and Tannat, respectively. The Merlot variety showed a double fit curve for the intraparticle diffusion model, indicating 2 main stages of biosorption. In the study of the isotherms, the Langmuir, Freundlich, Temkin and Dubinin - Radushkevich models were tested. The best model fit, as well as the parameter of each isotherm, were analysed. The Dubinin – Raduschkevich model showed the best fit for the two varieties tested. This model indicates a yeast with high porosity, being an adsorption of physical character, that is, occurring mainly by interactions of van Waals. In vitro digestion was evaluated for the degradability of the biosorbent flavonoids in yeast. In the gastric stage, the concentration of flavonoids decreased, which may be related to the chemical conditions gastric environment, in intestinal step the pH basic can change the compounds, generating new molecules with different biological activities. Thus, the yeast is interesting for incorporation of flavonoids, since she is able to protect them during the gastric phase and deliver them in the intestinal phase, where they will be absorbed.